Sosialisasi Metode Communicative Language Teaching (CLT) Dalam Komunikasi Bahasa Inggris di SMK Bina Jaya Palembang - Yuspar Uzer; Yus Vernandes; Marleni M; Fery Hidayad; Herlina H; Lefudin L; Haryogi Winarto; I Made Andika Bay (Yayasan Daarul Huda Kruengmane, 2026)
This Community Service Program (PKM) is entitled “The Socialization of the Communicative Language Teaching (CLT) Method in English Communication at SMK Binajaya Palembang.” The program incorporates the theory of Peter D. MacIntyre (2007), which explains the relationship between willingness to communicate, motivation, anxiety, and learning. The PKM employed a simulation-based approach through the practical implementation of learning activities related to the socialization of the Communicative Language Teaching (CLT) method in English communication at SMK Binajaya Palembang. The results of the program revealed that speaking activities generated positive responses in enhancing students’ willingness to speak. This was achieved through the principles of the CLT method, which place less emphasis on linguistic errors related to grammar, vocabulary, and pronunciation. Such an approach helps minimize students’ anxiety about making mistakes while speaking, thereby increasing their motivation to communicate in English confidently and without fear. As a result, students’ hesitation and unwillingness to communicate in English can be significantly reduced. Nevertheless, continuous guidance from teachers and students’ perseverance in practicing and learning remain essential to further improve their language proficiency and communication skills.